The additional role of anti-nucleosome antibodies in the prediction of renal damage in systemic lupus erythematosus based on CSTAR (XXV) - Ding, Yufang; Zhou, Yangzhong; Zhao, Jiuliang; Wu, Chanyuan; Zhang, Shangzhu; Jiang, Nan; Qian, Junyan; Zhang, Li; Li, Jing; Xu, Dong; Leng, Xiaomei; Wang, Qian; et al. (Lupus, 2024)
Objectives The predominant determinant of an unfavorable prognosis among Systemic Lupus Erythematosus (SLE) patients resides in the irreversible organ damage. This prospective cohort study aimed to identify the additional value of anti-nucleosome antibodies on organ damage accumulation in SLE patients. Methods Based on the Chinese SLE Treatment and Research group (CSTAR) registry, demographic characteristics, autoantibodies profiles, and clinical manifestations were collected at baseline. Follow-up data were collected by reviewing clinical records. Results Of 2481 SLE patients with full follow-up data, 663 (26.7%) were anti-nucleosome antibodies positive and 1668 (68.0%) were anti-dsDNA antibodies positive. 764 (30.8%) patients developed new organ damage during a mean follow-up of 4.31 ± 2.60 years. At baseline, patients with positive anti-nucleosome antibodies have a higher rate of lupus nephritis (50.7% vs 36.2%, p < .001). According to the multivariable Cox regression analysis, both anti-nucleosome (HR = 1.30, 95% CI, 1.09-1.54, p < .001) and anti-dsDNA antibodies (HR=1.68, 95% CI, 1.38-2.05, p < .001) were associated with organ damage accumulation. Anti-nucleosome (HR = 2.51, 95% CI, 1.81-3.46, p < .001) and anti-dsDNA antibodies (HR = 1.69, 95% CI, 1.39-2.06, p < .001) were independent predictors for renal damage. Furthermore, the combination of the two antibodies can provide more accurate information about renal damage in overall SLE patients (HR = 3.19, 95% CI, 2.49-4.10, p < .001) and patients with lupus nephritis at baseline (HR = 2.86, 95% CI, 2.29-3.57, p < .001). Conclusion Besides anti-dsDNA antibodies, anti-nucleosome antibodies can also provide information about organ damage accrual during follow-up. The ability of co-positivity of anti-nucleosome and anti-dsDNA antibodies in predicting renal damage may lead to additional benefits in the follow-up of these patients.